Iot-Based Real-Time Monitoring System For Enhancing Shrimp Pond Management: A Case Study In Deli Serdang, North Sumatra, Indonesia - Umurani, Khairul; ., Rahmatullah; Asfiati, Sri; Nasution, Arya Rudi; Saputra, Andrea; Putera, Tondi Amirsyah (Fakultas Teknik UMSU, 2025)
Monitoring shrimp ponds involves observing and measuring key environmental factors that influence shrimp health and growth. This study was conducted at a shrimp pond on Jalan Paluh Merbau, Tj. Rejo, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra, Indonesia. Traditionally, air humidity and water temperature are monitored manually by taking water samples for laboratory analysis or using litmus paper. These conventional methods are time-consuming and prone to inaccuracies, potentially compromising shrimp health. To address these challenges, this research implemented an Internet of Things (IoT)-based monitoring system to automate the measurement of air humidity and water temperature. The system utilizes DHT11 and DS18b20 sensors, integrated with an ESP32 module, to continuously collect data and automatically transmit it to Google Sheets for real-time monitoring. This IoT approach enables shrimp farmers to easily track water quality parameters, enhancing the accuracy and efficiency of pond management. A two-day testing phase demonstrated stable environmental conditions, with humidity levels recorded at 86.5% to 87.78% and water temperatures ranging from 27.55°C to 28.06°C. These readings were within the ideal thresholds for optimal shrimp growth, showcasing the system's effectiveness in maintaining suitable pond conditions. This research will contribute significantly to more efficient, accurate, and sustainable shrimp farming practices.